2003
DOI: 10.1094/mpmi.2003.16.9.827
|View full text |Cite
|
Sign up to set email alerts
|

Production of Substances by Medicago truncatula that Affect Bacterial Quorum Sensing

Abstract: Earlier work showed that higher plants produce unidentified compounds that specifically stimulate or inhibit quorum sensing (QS) regulated responses in bacteria. The ability of plants to produce substances that affect QS regulation may provide plants with important tools to manipulate gene expression and behavior in the bacteria they encounter. In order to examine the kinds of QS active substances produced by the model legume M. truncatula, young seedlings and seedling exudates were systematically extracted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
188
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 319 publications
(196 citation statements)
references
References 26 publications
1
188
0
3
Order By: Relevance
“…E. meliloti and a few other bacterial species have been reported to produce uncommon AHLs with long acyl chains, containing more than 12 carbons (Gonzalez and Marketon 2003;SanchezContreras et al 2007;Steindler and Venturi 2007;Venturi 2006). It is known that plants produce compounds that mimic AHLs, which are able to interfere with bacterial quorum sensing genes (Gao et al 2003;Hassan and Mathesius 2012;Teplitski et al 2000). In strains of S. fredii, R. etli, and R. sullae, the production of long chain AHLs was found to be enhanced in presence of their respective nod-gene-inducing flavonoid (Perez-Montano et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…E. meliloti and a few other bacterial species have been reported to produce uncommon AHLs with long acyl chains, containing more than 12 carbons (Gonzalez and Marketon 2003;SanchezContreras et al 2007;Steindler and Venturi 2007;Venturi 2006). It is known that plants produce compounds that mimic AHLs, which are able to interfere with bacterial quorum sensing genes (Gao et al 2003;Hassan and Mathesius 2012;Teplitski et al 2000). In strains of S. fredii, R. etli, and R. sullae, the production of long chain AHLs was found to be enhanced in presence of their respective nod-gene-inducing flavonoid (Perez-Montano et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Evaporation of AHL-containing droplets surrounding cell aggregates on leaves also would increase the concentrations of AHLs. Although studies have found that some plants can produce AHL mimics and inhibitors (24,25), no such compounds capable of affecting the QS of Pss were observed from bean leaves (26). Because the bean leaf surface is acidic from proton excretion (27), the instability of AHLs in alkali pH would not affect signal accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Plants have served as excellent systems in which to study microbe-microbe and interkingdom interactions. Plants produce compounds that serve as both autoinducer agonists and antagonists (260,261), and dozens of plant molecules, whose production profiles are found to change with the developmental stage of the plant, have been isolated and cataloged for their potential to interfere with bacterial signaling (262). For example, exudates from alfalfa seeds (Medicago spp.)…”
Section: Natural-product Qs Inhibitorsmentioning
confidence: 99%